Long-term follow-up after lens-sparing vitrectomy for complications of retinopathy of prematurity - Lingam Gopal; Pramod Bhende; Chetan Rao; Parveen Sen; Tarun Sharma; Debarati Dasgupta (Indian Journal of Ophthalmology)
Purpose: To report the long-term anatomical and functional results of lens-sparing vitrectomy (LSV) for stage 4 retinopathy of prematurity (ROP). Design: Retrospective study. Methods: This is a study of 23 eyes of 16 patients with stage 4 ROP who underwent lens-sparing vitrectomy at a tertiary care center and had a minimum of 2 years of follow-up. The main outcome measures are the retinal status and visual outcome at the final follow-up. Results: After a mean follow-up of 7.36 years, the lenses remained clear in 69.57%; anatomical success in terms of the attached retina was achieved in 19/23 eyes (82.61%) and vision of ≥6/24 was achieved in 8/23 eyes (34.78%), whereas navigational vision (≥1/60) was achieved in 16/23 (69.56%). The mean spherical equivalent was −8.50 + 6.39 diopters. High myopia (≥7 dsph) was noted in 43.47% of patients. The severity of myopia was not related to previous lasers and was less severe in eyes with posterior pole residual folds compared to normalized fundus or eyes with macular drag but no fold. At the final follow-up, 3/16 (18.75%) patients had bilateral blindness due to total retinal detachments and 11/16 (68.75%) had recorded functional vision in one or both eyes, whereas two others could potentially be having vision but could not be evaluated. Conclusions: The long-term results of lens-sparing vitrectomy for stage 4 ROP are favorable with a majority retaining clear lenses and attached retina and two-thirds having functional vision.